Formulation of a fast dissolving larvicidal tablet using the water-soluble extractives of Azadirachta indica A. Juss leaves - Arrosas, Ronald Henry Ian T.
Dengue has become the most relevant mosquito-borne viral disease in recent time. It is caused by the dengue virus, all four steriotypes of which are transmitted to human through the bites of infected female Aedes aegypti mosquitoes. Previous studies have demonstrated the activity of neem (Azadirachta indica A. Juss) limonoids towards Aedes aegyti larvae, the use of which do no elicit nagative consequences to the environment. This study aimed to develop a fast dissolving tablet (FDT) using the water-soluble extractives of Neem leaves for the control of the said mosquito vector. This included the determination of a minimum concentration that effects larvicidal action, the determination of compatible tablet excipients to be use in the manufacture of FDT's the evaluation of quality control attributes and finally, the evaluation of the larvicidal action of formulated tables. Initial processing included the extraction of plant constituents using pH 4.0 phosphate buffer solution and the lyophilization of such extract to preserve the active constituents from hydrolytic degration. The extract contain tannins, glycosides and reducing substances as determined through phytochemical testing. The LC50, LC90 and LC99 values were 3.0137% w/v, respectively , as determined through lethality bioassays on 3rd instar larvae. The necessity for thermal and moisture regulated storage conditions for products of the lyophilized extract were indicated by stability test. The formulated tablets proved to be effective again Aedes aegypti larvae, such is attribute to the synergistic effect of film-facilitated suffocation of neem polysaccharides and the direct larvicidal effects of neem limonoids. The result of this study thus established the potential of the formulated tablets in dengue vector control efforts.